BRIDGING GAP OF USER GOAL REQUIREMENTS AND IMPLEMENTED APPLICATIONS BASED ON FEATURE MODEL - Ahmad Nurul Fajar; Eko K. Budiardjo; Zainal A. Hasibuan (Faculty of Computer Science Universitas Indonesia, 2012)
Feature modeling is a conceptual thinking for identifying and classification feature in order for support software product lines. However, there are lack of the user goal requirements. It related with a technique for managing of features commonalities and variability. It has a hierarchy of features with variability and the purpose is to organize features. In practice of implemented applications, the feature model development lack of goal user requirement. The goal of user requirement in Indonesian government has described in document regulations. It should be a fundamental concern to develop e-government applications. However, In order to capture degree of software feature importance, some of features compared with implemented e-government applications. We have extracted some of features which can be compared with the implemented e-government applications. Our technique is extracted are derived from document regulations to business process model and feature model also. We Choose SIPKD and SIMDA applications which has implemented in Indonesian local government which has variation from one and another. We use extended AHP and S-AHP to find the prioritization of software features. The results are 80 features in SIPKD and 90 features in SIMDA. There are 65 features common and 25 variant features .This make un-optimization usage applications.